Sistem Pendukung Keputusan Pemilihan Sales Marketing Terbaik di PT. Alfa Scorph Menggunakan Metode COPRAS - Siregar, Alwali Daini Udda; Hasibuan, Nelly Astuti; Fadlina, Fadlina (STMIK Budi Darma, 2020)
Of the various functions that exist in a company engaged in the business world, the function of marketing or marketing functions is a very vital and strategic function for the company concerned. The rapid development of the business world, accompanied by increasingly intense business competition, has actually strengthened the position of the marketing aspect of this vital and strategic position, Sales are the jobs most needed by the company, these 10 specialties, total vacancies for sales are 19%, followed by financial default by 18%, while IT / communication amounts to 13%. Job vacancies as sales are widely available, but lack of interest, therefore companies find it difficult to find employees in the sales department The COPRAS method assumes a direct and proportional dependence on the level of significance and utility of the alternatives in the presence of conflicting criteria. This takes into account the performance of alternatives with respect to different criteria and also the weight of the appropriate criteria. This method chooses the best decision considering the ideal and ideal solution - worst. The COPRAS method used here for decision making in the manufacturing environment adopts a six-stage procedure ranking and evaluates alternatives in terms of their level of importance and usefulness. The COPRAS method has the ability to take into account positive (favorable) and negative (unfavorable) criteria, which can be assessed separately in the evaluation process. The most important feature that makes the COPRAS method superior to other methods is that it can be used to calculate the level of alternative utility that shows the extent to which alternatives are taken for comparison